Degradation of antibiotics amoxicillin by Co3O4‐catalyzed peroxymonosulfate system. Issue 2 (21st March 2012) - Guo, Weilin; Su, Shengnan; Yi, Chunliang; Ma, Zhenmin
<x xml:space="preserve">Abstract</x> Sulfate radical‐based advanced oxidation processes (SR‐AOPs) are attracting considerable attention due to the high oxidizing ability of sulfate radical to degrade organic pollutants in aqueous environments. In this study, the degradation of antibiotics amoxicillin using SR‐AOPs was investigated. This process is based on the generation of sulfate radicals through Co3O4‐mediated activation of peroxymonosulfate (PMS). Several parameters affecting antibiotics degradation such as Co3O4, PMS, pH, and temperature were investigated. The optimal conditions were found to be as follows: oxone concentration 0.01 mol·L −1, Co3O4 dosage 0.06 g, pH 6.0, reaction temperature 60°C, and reaction time 45 min. Under these optimum conditions, it was found that the chemical oxygen demand (COD) removal efficiency of 91.01% was achieved. The effect of ultrasound in the Co3O4/PMS system for amoxicillin degradation was also studied. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 193‐197, 2013